2017
DOI: 10.1039/c7ra03665e
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Pd supported on 3D porous carbon for enhanced selective oxidation of benzyl alcohol

Abstract: A 3D porous carbon framework (PCF) supporting palladium nanoparticles (Pd/PCF) was synthesized by a simple and economical method and used for catalyzing benzyl alcohol oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…046-1043) is observed in the pattern of CdS–TiO 2 /Pd ternary nanocatalyst, which corresponds to metallic Pd (Figure d). This confirms the formation of CdS–TiO 2 /Pd ternary nanocatalyst . The average crystallite size calculated using the Scherrer formula is found to be 30.12 nm for (b), 27.81 nm for (c), and 27.69 nm for (d).…”
Section: Resultssupporting
confidence: 71%
“…046-1043) is observed in the pattern of CdS–TiO 2 /Pd ternary nanocatalyst, which corresponds to metallic Pd (Figure d). This confirms the formation of CdS–TiO 2 /Pd ternary nanocatalyst . The average crystallite size calculated using the Scherrer formula is found to be 30.12 nm for (b), 27.81 nm for (c), and 27.69 nm for (d).…”
Section: Resultssupporting
confidence: 71%
“…XPS peaks of Pd 3d 3/2 and Pd 3d 5/2 , centered at 340.2 and 335.1 eV (Fig. 1e ), suggest that Pd 0 is the dominant component with minor Pd 2+ coexisting on the Pd–CM surface 41 , possibly due to surface oxidation. Similarly, the deconvoluted peaks of Pt 4f 5/2 and Pt 4f 7/2 at binding energies of 74.8 and 71.5 eV (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…00-041-1049). The additional peak observed at 2θ = 39.4° for TNC-I and 2θ = 39.8° for TNC-II confirmed the successful loading of Pd on the surface of CdS@TiO 2 nanocomposites, 31,32 and it was observed that the crystallinity is retained after the loading of Pd as shown in Figure 1. The average particle size was calculated using the Scherrer formula, 33 which was found to be 10.26 nm ( TNC-I ), 7.31 nm ( TNC-II ), 30.5 nm ( BNC-I ), and 13.3 nm ( BNC-II ) for as-prepared nanocomposites.…”
Section: Resultsmentioning
confidence: 57%